Sectoral Linkages in Pangandaran Regency’s Regional Development - Hendriany, Reni; Pravitasari, Andrea Emma; Rustiadi, Ernan (Universitas Negeri Semarang, 2024)
Pangandaran District is a newly formed region in West Java Province. Effective and competitive regional development requires support from the potential leading sectors in a region. Prioritization is needed because of limited resources that cannot facilitate the development of all sectors simultaneously. This analysis aims to identify leading sectors, sector interconnections, and multiplier effects on the economy of Pangandaran Regency. The results are that there are 5 (five) sectors that are comparatively and competitively superior, namely: (1) Accommodation, Food and Drink Providers, (2) Agriculture, Forestry and Fisheries (3) Transportation and Warehousing, (4) Wholesale and retail trade , Repair and (5) Real Estate. The largest backward linkages are achieved by the